Effect of water deficit and elevated temperature on pollen development of drought sensitive and tolerant winter wheat (Triticum aestivum L.) genotypes - Jäger, Katalin; Fábián, Attila; Barnabás, Beáta (Acta Biologica Szegediensis, 2008)
The effects of meiotic water deficit and combined heat and drought stress were studied on microsporogenesis and fertility of wheat. Among normal pollen, 12% of the drought stressed tolerant Plainsman V and 34% of the sensitive Cappelle Desprez pollen were arrested at early stages of gametogenesis. Drought stress manifested in significant reduction of the mean fertility in both sensitive (41%) and tolerant (33%) genotypes. Combined stress applied during meiosis among developmental arrests caused serious morphological anomalies in the sensitive genotype. When plants of the Plainsman V variety were subjected to simultaneous drought and heat, additional 24% significant decrease occurred in the ratio of normal pollen. The fertility of the basal part of the spikes was similar to the control in both genotypes, but the seed set in the middle and on the top of the spikes decreased significantly as a consequence of combined drought and heat stress.